2017
DOI: 10.11613/bm.2017.043
|View full text |Cite
|
Sign up to set email alerts
|

Detection of let-7 miRNAs in urine supernatant as potential diagnostic approach in non-metastatic clear-cell renal cell carcinoma

Abstract: IntroductionUrinary microRNAs (miRNAs) are emerging as a clinically useful tool for early and non-invasive detection of various types of cancer. The aim of this study was to evaluate whether let-7 family miRNAs differ in their urinary concentrations between renal cell carcinoma (RCC) cases and healthy controls.Materials and methodsIn the case-control study, 69 non-metastatic clear-cell RCC patients and 36 gender/age-matched healthy controls were prospectively enrolled. Total RNA was purified from cell-free sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 10 publications
3
36
0
Order By: Relevance
“…Urinary cell-free miRNAs are emerging as potential biomarkers of urologic cancers [7]. In our previous study, we have shown that cell-free miRNAs are abundant in urine of renal cell carcinoma patients and present promising non-invasive biomarkers [9]. Similarly, several reports described specific miRNA expression profiles in urine of patients with BCA indicating their potential usage for early detection of the disease, prognosis prediction or therapy response [10][11][12].…”
Section: Discussionmentioning
confidence: 94%
“…Urinary cell-free miRNAs are emerging as potential biomarkers of urologic cancers [7]. In our previous study, we have shown that cell-free miRNAs are abundant in urine of renal cell carcinoma patients and present promising non-invasive biomarkers [9]. Similarly, several reports described specific miRNA expression profiles in urine of patients with BCA indicating their potential usage for early detection of the disease, prognosis prediction or therapy response [10][11][12].…”
Section: Discussionmentioning
confidence: 94%
“…Several miRNAs including miR-210-3p were upregulated in urine from transitional cell carcinoma patients and capable to facilitate cancer diagnosis [ 69 ]. All members of let-7 families were significantly elevated in urine from clear-cell renal cell cancer (ccRCC) patients [ 70 ], while a combination of urinary exosomal miR-34b-5p, miR-126-3p, and miR-449a-3p could be favorable for ccRCC diagnosis [ 71 ]. A panel of four breast cancer-related miRNAs (miR-21-5p, miR-125b-5p, miR-155-5p, and miR-451-5p) was also differentially expressed in urine samples of breast cancer patients and exhibited their diagnostic value [ 72 ].…”
Section: The Advantage Of Circulating Mirnas As Diagnosis and Prognosmentioning
confidence: 99%
“…Besides the studies from our group using urine for the detection of RCCs by high levels of miR-15a [ 19 ], there are only two other reports in renal cancer using the urine as material for a liquid biopsy. Fedorko et al [ 71 ] detected let-7 miRs in urine supernatant as a potential diagnostic approach in nonmetastatic clear cell renal cell carcinoma. A second study by Butz et al [ 72 ] screened urinary miRs for differential diagnosis between patients with renal tumors (malignant and benign) and controls.…”
Section: Discussionmentioning
confidence: 99%